Analisis Maslahah dan Akuntabilitas sebagai Prinsip Manajemen Aset Wakaf Kontemporer - Julianinggar Lusiana Isnaini; Hapsari Wiji Utami (Management of Zakat and Waqf Journal (MAZAWA), 2020)
Digital technology is increasingly fast and easy to create great opportunities for caring action and socio-philanthropic activities. This development has also become a motivation for zakat institutions in order to improve and increase their management activities oriented towards improving strategic management, so that their existence can continue and expand. All opportunities for new strategies and approaches are optimally absorbed and implemented so that they can be carried out without taking long. Coupled with the role of the state as a regulator by making laws and regulations and the implementation of zakat management run smoothly and orderly and further increasing the innovation of zakat management institutions, especially amil in its management, including the distribution of zakat benefits. Using a qualitative literature study research method, the researcher intends to analyze (1) Islamic law studies related to zakat management including distribution and utilization, then formulate (2) zakat empowerment strategies, so that (3) empowerment program designs for the poor are based on MUI Fatwa Number 14. 2011 concerning the Distribution of Zakat Assets in the Form of Managed Assets. Researchers obtained primary data sources through the interaction of online communication media with several devices in zakat institutions when researchers were doing internships. Secondary data comes from journal articles, scientific papers, and papers accessed via the internet. As a result, the preparation of empowerment program planning needs to pay attention to the provisions of the MUI Fatwa Number 14 of 2011 which applies and requires a mature management strategy in all series of activities, coupled with appropriate and competent resources, principles of innovation and full creativity in management so that program design can be realized in accordance with legal provisions regulating the optimal allocation of zakat assets so as to be able to grow an independent generation of dhuafa.